Low-power Wireless Security System in the Home Automation - Pham, Manh Thang (H. : ĐHQGHN, 2017)
Wired networking has been used in home automation for many years and proven to be reliable. Wireless has only recently become a viable option for home automation thanks to improved reliability and reduced cost. Today there are many scenarios where wireless is a viable and preferable option, such as hard-to-wire or expensive-to-wire locations, interconnecting multiple buildings, and need for mobility.